Freestanding Membranes of Titania Nanorods, Photocatalytically Reduced Graphene Oxide, and Silk Fibroin: Tunable Properties and Electrostatic Actuation - Finn Dobschall; Hauke Hartmann; Sophia Caroline Bittinger; Norbert Schulz; Hendrik Schlicke; Hoc Khiem Trieu; Tobias Vossmeyer (Advanced Electronic Materials)
Abstract In this study, the mechanical properties of freestanding membranes made of graphene oxide (GO), titania nanorods (TNRs), and silk fibroin (SF) are investigated and their application is demonstrated as electrostatically driven actuators. Using a stamping process, the membranes are transferred onto substrates with circular apertures or square cavities measuring ∼80 to 245 µm in diameter or edge length, respectively. Afterwards, the membranes are exposed to deep‐UV (DUV) radiation in order to photocatalytically convert GO to reduced graphene oxide (rGO). Microbulge tests combined with atomic force microscopy (AFM) measurements reveal enhanced mechanical stability after the DUV treatment, as indicated by an increase of Young's modulus from ∼22 to ∼35 GPa. The toughness of the DUV‐treated membranes is up to ∼1.25 MJ m−3, while their ultimate biaxial tensile stress and strain are in the range of ∼377 MPa and ∼0.68%, respectively. Further, by applying voltages of up to ±40 V the membranes are electrostatically actuated and deflected by up to ∼1.7 µm, as determined via in situ AFM measurements. A simple electrostatic model is presented that describes the deflection of the membrane as a function of the applied voltage very well.